PERANAN PONDOK PESANTREN SEBAGAI LABORATORIUM DEMOKRASI DALAM MEMBANGUN NILAI MORAL PANCASILA : Studi Deskriptif Di Pondok Pesantren Santi Asromo Islamic Boarding School di Kabupaten Majalengka - Wiwit Khairunisa Pratiwi, - (2018)
Di era moderenisasiinibanyakterjadifenomenamerosotnyanilai-nilai moral dalamkehidupanremaja di Indonesia.Kasuskenakalanremajasemakinmengkhawatirkan, agar kenakalanremajainitidaksemakinparahmakaperluadanyabimbingandanpendekatansecarapsikologis.Untukitudiperlukanadanyapembinaanakhlakdikalanganremaja.Pembentukankarakterdanpembinaanakhlakbangsabisadilakukanmelaluilembagapendidikanyaitupesantren.Penelitianinimenggunakanpendekatankualitatifdanmenggunakanmetodestudikasus.Adapunteknikpengumpulan data yang digunakanadalahobservasi, wawancara, studidokumentasi.studi literature dancatatanlapangan. Penelitianinidilaksanakan di PondokPesantrenSantiAsromo Islamic Boarding School di kabupatenMajalengka, subjekpenelitiannyayaitukepalasekolah SMA PrakaryaPesantrenSantiAsromo, pembinaasrama, guru PendidikanKewarganegaraan, orang tuasantridanparasantidansantriwatipondokpesantrensantiasromo. Hasildaripenelitianiniadalahbentukkegiatanupayamembangunnilai moral di pondokpesantrensantiasromoitumelalui 3 kegiatanyaitukegiatan di asrama, di sekolahdankegiatanektrakulikuler.Upayamembangunnilai moral Pancasila di sekolahdandiasramadiantaranyadilakukandalambentukpembiasaan, sepertisantridiwajibkanuntukselalumelakukansholatberjamaah, setiappagiharidiwajibkanuntukberdzikirbersama, danberakhlakmulia.Sedangkankegiatanekstrakulikuleryaitudalamkegiatanektrakulikulerpesertadidikdiwajibkanuntukdatangtepatwaktu, dalamkegiatanekstrakulikulermemilikiketerkaitandenganmembangunnilai moral Pancasilasepertimembiasakanpesertadidikuntukbersikapdisiplin, mandiri, peduli, danbertanggungjawab.Kesimpulandaripenelitianiniadalahbahwapenanamannilai moral Pancasilapesertadidik di PesantenSantiAsromosudahberjalandenganbaikdandapatdikatakantelahberhasildilaksanakan. Serta memperolehhasiloutput yang sesuaidengantujuanpembentukankarakteryaituterbentuknyakarakter religious, disiplin, kerjakeras, mandiridansalingmenghormatidari proses pembentukankaraktermelaluiupayapenanamannilai-nilai moral Pancasila. ------------------------------------------------- In this modernization era, there are many phenomena of the decline of moral values in the lives of teenagers in Indonesia. Juvenile delinquency cases are increasingly alarming, so that juvenile delinquency is not getting worse, it is necessary to have psychological guidance and approach. For this reason, moral guidance is needed among adolescents. Character building and national moral development can be done through educational institutions, namely pesantren. This study uses a qualitative approach and uses a case study method. The data collection techniques used are observation, interview, documentation study. literature studies and field notes. The research was conducted at the SantiAsromo Islamic Boarding School Islamic Boarding School in Majalengka district, the subject of the research was the head of a Prasetya High School school, PesantrenSantiAsromo, boarding house teacher, Civics Education teacher, santri parents and santi and santriwatisantiasromo Islamic boarding school.The results of this study are a form of activities to build moral values in the santiasromo Islamic boarding school through 3 activities, namely activities in the dormitory, in school and extracurricular activities. Efforts to build the moral values of Pancasila in schools and dormitories are carried out in the form of habituation, such as santri are obliged to always pray together, every morning are obliged to dhikr together, and have noble character. While extracurricular activities, namely in extracurricular activities, students are required to arrive on time, extracurricular activities are related to building Pancasila moral values such as familiarizing students to be disciplined, independent, caring and responsible. The conclusion of this study is that the cultivation of Pancasila moral values of students in PesantenSantiAsromo has been going well and can be said to have been successfully implemented. As well as obtaining outputs that are in accordance with the objectives of character building, namely the formation of religious, disciplined, hard-working, independent and respectful characters from the process of character building through efforts to instill Pancasila values.